Estudo comparativo entre os Enantiômeros da Carvona em Modelos de Inflamação Aguda e de Hipersensibilidade Imediata - Oliveira, Juliana da Silva Brandi (2011)
Enantiomers are asymmetric compounds that present mirror images of each other, not overlapping and different behaviors in chiral environments, resulting in esterioseletiva discrimination and different biological effects. The carvone is a monoterpene, a constituent of many essential oils found in nature as two enantiomers, (S)-(+)-carvone and (R)-(−)-carvone. The inflammation, a physiological response of the organism, when it occurs exaggerated or inappropriated ways may promote tissue damage and associated pathologies. An example of inflammatory disease is asthma, an immediate hypersensitivity process of the airways and the conventional treatments have significant adverse effects. The aim of this study was to evaluate the carvone enantiomers in experimental models of inflammation and hypersensitivity of the airways. To investigate the effect anti-inflammatory the following parameters were evaluated: NO production by cells J774.A1, paw oedema formation induced by carrageenan, zymosan, compound 48/80 and histamine, cell migration and cytokines production (TNF-α and IL-1β) in the experimental model of peritonitis induced by zymosan in Swiss mice. To evaluate the anti-asthmatic activity of these enantiomers, it was used the experimental model of asthma induced by ovalbumin and the following parameters were analyzed: bronchoalveolar lavage (BAL), mucus production, OVA-specific IgE synthesis, cytokine production (IL-13, IFN-γ and IL-10). The results showed that both enantiomers were able to reduce NO production, inhibit the paw oedema induced by phlogistic agents and inhibit cell migration to the peritoneum, but only the (R)-(−)-carvone was able to reduce levels of TNF-α. In the murine model of asthma, the (R)-(−)-carvone, was able to reduce the cellularity of the BAL, modulate the OVA-specific IgE production, reduce the cell infiltration and mucus in the lungs and further increase the IL-10. However, although the (S)-(+)-carvone has reduced the BAL cellularity and increased IFN-γ levels, it was unable to reduce the cell infiltration in the lung and increase the mucus production. Therefore, both enantiomers of carvone showed anti-inflammatory effect, although only the (R)-(−)-carvone showned potential anti-asthmatic. Additionally, the results presented by (S)-(+)-carvone, revealed a potential adverse effect of this enantiomer in the experimental model of asthma.